USE OF FISBALL GAME: A STRATEGY TO IMPROVE SELF- CONCEPT OF VOCATIONAL HIGH SCHOOL LEARNERS - Rizal, Agus; Amelia, Mega Putri; Khoirun, Nadliroh; Arifah, Siti; Maulida, Salma Nur (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
Many vocational high school students struggle to understand their self-concept, which affects their ability to adapt academically and socially. Purpose of this study aimed to develop and validate Fisball D’Brooks, a game-based guidance and counseling media grounded in William D. Brooks’ self-concept theory to support students with low self-concept. Methods of this study employed a Research and Development (R&D) design using the Borg & Gall model. The development involved expert validation (media and material experts), practitioner review, and field trials. Data were collected using feasibility checklists and student feedback. Results show The product achieved high feasibility scores from experts (usability = 93.75%, feasibility = 87.5%, accuracy = 95%, overall validity index = 92%, categorized as very valid). Students reported increased awareness of their strengths and weaknesses and showed higher engagement in guidance sessions. Conclusion of this study Fisball D’Brooks is a practical and valid media that supports guidance learning and helps students improve their understanding of self-concept